La discusión sobre el canibalismo y los sacrificios humanos en la disputa de Sepúlveda con las casas (1550-1551) (2009)
The proposal of this paper is to offer an analysis of the discussion about the cannibalism and the native human sacrifices in the contest of the controversy between Las Casas and Sepúlveda. This analysis is very relevant, because it allows observing the roots more distant of the actual law of intervention and the doctrine of the human rights. For that effect, the author begins with a fast description of the causes that drove to the fight of Valladolid, at the same time that enunciates the four points in discussion. In second place, is realized a description more or less detailed of the fourth argument of the controversy, which treats about the human sacrifices and the native cannibalism. And it concludes showing that, explaining these practices, Las Casas looks for the integration of the native cultures in the general mark of the historic universal knowledge.Key Words: Cannibalism, human sacrifices, natural law, right war.